As composições de Francisco Padilha: uma proposta de Songbook para a prática de Big band da Escola de Música do estado do Maranhão “Lilah Lisboa de Araújo” - GOMES , Thales Márcio Vale (2024)
This work is the result of research into the work of the composer, conductor, trumpet player and Prof. Dr. Antônio Francisco de Sales Padilha. In this sense, its general objective is to prepare a Songbook, with works by Francisco Padilha, to be used as teaching material in the Big Band practice discipline at the Maranhão State Music School “Lilah Lisboa de Araújo”. Thus, its specific objectives are: a) Identify musical works by Francisco Padilha, characterizing them from their context in their historical and sociocultural aspects in Maranhão; b) Adapt the works of Francisco Padilha for a Big Band formation, based on his rhythms and musical aesthetics and, from there, making a contribution to student learning; and c) Demonstrate, through musical arrangements, how Francisco Padilha's works - his compositional elements - can be used in Big Band practice at EMEM. The problem question to be answered is: How can Francisco Padilha's compositions be organized in a Songbook in order to contribute to the learning of music and instrumental performance in Big Band practice? The methodology used is a qualitative approach and documentary research. As for the theoretical foundation used, it was based on authors who refer to Big Bands, jazz, Escola de Música do Estado do Maranhão “Lilah Lisboa de Araújo”, Prof. Dr. Antônio Francisco de Sales Padilha, among others. Throughout the research, I present the Songbook “Interlude for a beautiful girl – Works by Francisco Padilha adapted for Big Band”, one of the results of the research that will contribute to teaching in a Big Band format group or smaller groups that will also record the music instrumental produced in Maranhão by a composer from Maranhão who uses topics from Maranhão music, interweaving them with other topics already known in other places.